PENGARUH TEPUNG DAUN CENGKEH TERHADAP PERTUMBUHAN DAN HASIL TOMAT ORGANIK - Evita . (Bioplantae, 2012)
The aimed of this research to exmaine  of  the effect of colve  leaves powder on the growth and yield of organik tomatoes. This research was cunducted  in Randomized block design, with five treatments of cinnamon powder dosage and four replication. The cinnamon powder dosage  are, c0 =  0.0 g plot-1 , c1 =  250.0 g plot-1, c2 =  500.0 g plot-1 , c3 =  750.0  g plot-1, c4 = 1000.0 g plot-1 . The parameters observed are plant height,  time of flowering and fruitset, root dried  weight, plant dried  weight and plant yield. The result showed that, there no signicantly differences between treatment on growth parameter. The significantly effect only achived on yield component. The highest tomatoes yield and the number of tomatoes was achieved at dosages  500.0 g plot-1colve  leaves powder   Key words : Leaves powder, tomato, organic